2020
DOI: 10.1088/1742-6596/1655/1/012064
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and Skills of Science Teachers’ Online Teaching through Online Learning Training in The Covid-19 Period in Pekanbaru Indonesia

Abstract: The purpose of this study was to analyze the motivation and skills of science teachers' online teaching through online teaching mentoring training in Pekanbaru in the month of May-July 2020. The subject of this descriptive study was the teachers participating in the training. Online training materials include Google classroom, Google form, slides, and videos. The training used the methods of simulation, training, modeling, and production of science teachers' online teaching videos. The research parameters were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A lot of training is carried out in an effort to improve educators skills, including training on the ability of teachers in the field of technology-based media (Wahjusaputri & Bunyamin, 2020). Improving teacher skill through virtual reality learning media (Handayani et al, 2020), training and mentoring online learning for teacher and professional educators in Pekanbaru (Taufik & Yustina, 2020).…”
Section: Need Assessment Resultsmentioning
confidence: 99%
“…A lot of training is carried out in an effort to improve educators skills, including training on the ability of teachers in the field of technology-based media (Wahjusaputri & Bunyamin, 2020). Improving teacher skill through virtual reality learning media (Handayani et al, 2020), training and mentoring online learning for teacher and professional educators in Pekanbaru (Taufik & Yustina, 2020).…”
Section: Need Assessment Resultsmentioning
confidence: 99%
“…In addition, research during the COVID-19 epidemic has been found to show that online mentoring training is effective in increasing the motivation and online teaching of science teachers' skills during the COVID-19 period [53]. Hence, it can be expected that technical support in remote learning for selected surveyed academic teachers, regardless of the period of the epidemic, would bring positive results.…”
Section: Discussionmentioning
confidence: 99%